A de novo sacrificial-MOF strategy to construct enhanced-flux nanofiltration membranes for efficient dye removal. (2nd November 2020) - Yang, Fan; Sadam, Hussain; Zhang, Yanqiu; Xia, Jianzhong; Yang, Xiaobin; Long, Jun; Li, Songwei; Shao, Lu
Graphical abstract: Highlights: MOFs were sacrificed to tune nanoporous channels in the selective layer. The GA/sZIF-67/PPy NF membrane demonstrated a flux enhancement of 745%. The developed membrane had the good stability during long term test. The de nova NF membrane exhibited excellent permeance for dye removal. Abstract: Nanofiltration membanes play a critical role in alleviating global water scarcity, affecting more than 4 billion people. Herein, a new metal organic framework (MOF) sacrificicial strategy is designed to synthesize flux-enhancing nanofiltration membrane for efficient dye removal. With the aid of polyphenol chemistry, ZIF-67 MOF was first coated onto a porous support and in situ transformed into a selective layer by virtue of pyrrole polymerization. Trigerred by ammonium persulfate, polypyrrole selective layer functioalized nanofiltration membrane was fabricated when accompanying pore regulation by MOF self-sacrifice. The membrane demonstrated a flux enhancement of 745% than pristine polypyrrole (PPy) one with maintained rejection. Furthermore, the synergistic interactions among polypyrrole, polyphenol, and porous support endowed membrane with excellent stability during long term test. The designed MOF sacrificed route may open a new avenue for fabricating advanced energetic-efficient membranes with the reconstructed architecture towards diverse separation applications.